2020
DOI: 10.1007/s42452-020-03504-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuO, MoO3 and ZnO nanomaterial coated absorbers for clean water production

Abstract: Solar energy is one of the most powerful sources for many sustainable applications. Recently, efficient water distillation has attracted significant attention. The fresh water productivity depends on how efficiently the system harvests the incoming solar energy and converts it into useful heat. In the present work, nano-coated absorber plates (NCAPs) were examined in the single slope solar still (SSSS) for clean water production. The NCAPs were CuO, MoO 3 and ZnO, respectively. The CuO-NCAP was fabricated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Daily variation of the irreversibility rates was determining using equations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and is presented in this section, as follows. Fig.…”
Section: Energy Exergy and Irreversibility Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Daily variation of the irreversibility rates was determining using equations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and is presented in this section, as follows. Fig.…”
Section: Energy Exergy and Irreversibility Analysismentioning
confidence: 99%
“…With pioneering advances in material science and nanotechnology in recent years, research has focused on improving the water generation potential of SS using coatings on the absorber and condenser to facilitate both evaporation and condensation. As absorber coatings, nano-SiO2, nano-TiO2, micro Cu, Al, and Sn were most widely used to date [11][12][13][14][15] to enhance the solar absorptivity and thermal performance of the SS. The nanoparticles coated surfaces exhibited excellent conductivity and increased the water generation rate of SS.…”
Section: Introductionmentioning
confidence: 99%
“…With significant development in materials science and nanotechnology, various researches have explored the role of coating the SS absorber using nanoparticles for increasing the solar absorption and augmenting the water yield. Arunkumar et al [19] explored ZnO, CuO, MoO3 as coating materials for the solar absorber and examined their effects on the water yield of the SS. It was found that the CuO coated SS exhibited the highest water yield amongst all coatings tested.…”
Section: Introductionmentioning
confidence: 99%
“…A maximum temperature of around 70°C has been reported in outdoor conditions (Kabeel et al, 2017). Other nanoparticles with different morphologies, i.e., sphere-shaped Cu 2 O, plate-like MoO 3 , and wedge-shaped ZnO, have been employed with increased surface temperature and water yield (Arunkumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%